Mechanisms of Standardization Effect on Innovation - Grinyov, B.V.; Lyubinskiy, V.R.; Danylenko, Yu.A.; Zhikhareva, O.V. (Science and Innovation, 2024)
The impact of standardization on innovation processes has been discussed. The effect of standards on the growth of national economy in various countries has been surveyed. The analysis of what is primary, the innovation or the standards, has been made. The inconsistency of standardization and innovation has been considered; the reasons therefor are explained; and a method for its prevention has been proposed.